2020
DOI: 10.1039/c9ta10964a
|View full text |Cite
|
Sign up to set email alerts
|

Defect chemistry of disordered solid-state electrolyte Li10GeP2S12

Abstract: Most solid-state electrolytes exhibit significant structural disorder, which requires careful consideration when modeling the defect energetics. Here, we model the native defect chemistry of a disordered solid electrolyte, Li10GeP2S12.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
2
42
1
Order By: Relevance
“…Previous investigations of native defects in SEs have put emphasis on strategies to improve ionic conductivity. [54][55][56]68,69 In this study, we focus on all native defects that may alter the concentration of charge carriers (electrons, holes), in addition to ionic carriers i.e., Li + and Na + ions. In a previous study, 55 we found V Na +Li +…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations of native defects in SEs have put emphasis on strategies to improve ionic conductivity. [54][55][56]68,69 In this study, we focus on all native defects that may alter the concentration of charge carriers (electrons, holes), in addition to ionic carriers i.e., Li + and Na + ions. In a previous study, 55 we found V Na +Li +…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, here, we treat SEs as materials with finite band gaps. 54,55 As such, the defect theory developed for semiconductors can be applied to calculate the defect energetics in SEs. 55,56…”
Section: Point Defects and Electronic Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Their computational studies were very useful for researchers studying sulfide electrolytes and led to better understanding of the stability of the electrolyte and electrode materials. In addition, Hu et al [274] and Du et al [275] performed computational analysis on LGPS-type structures, Binninger et al [276] investigated the electrochemical stability window of LGPS-type structures, and Gorai et al [277] performed electronic structure and defect chemistry calculations for LGPS-type structures.…”
Section: Li7p2s8imentioning
confidence: 99%
“…Li 11−x M 2−x P 1+x S 12 (M = Ge, Sn, Si) (LGPS)-Type StructuresIn 2011, Kamaya et al[266] synthesized the Li 10 GeP 2 S 12 (LGPS) solid electrolyte and reported a conductivity of 9 × 10 -3 S cm −1(Table 1)and electrochemical properties of a LiCoO 2 -LGPS|LGPS|In cell. Moreover, other researchers have extensively analyzed this system[267][268][269][270][271][272][273][274][275][276][277].LGPS presented tetragonal crystal structure with the lattice parameters a = 8.708 Å and c = 12.605 Å and consisted of negatively charged PS4 3− and GeS 4 4− tetrahedra surrounded by (mobile) Li + ions for charge compensation as shown inFigure 17a,and X-ray powder diffraction patterns and Rietveld refinements of Li 11 Si 2 PS 12 and Li 10 SnP 2 S 12 are compared with those previously reported for Li 10 GeP 2 S 12 and Li 7 GePS 8 in…”
mentioning
confidence: 99%